2011
DOI: 10.1002/jmri.22405
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast‐enhanced MRI of primary rectal cancer: Quantitative correlation with positron emission tomography/computed tomography

Abstract: Purpose: To assess the correlations between parameters measured on dynamic contrast-enhanced magnetic resonance imaging and 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) in rectal cancer. Materials and Methods:To assess the correlations between parameters measured on dynamic contrastenhanced MRI and FDG-PET in rectal cancer.Results: Significant correlations were only demonstrated between k ep and SUVmax (r ¼ 0.587, P ¼ 0.001), and k ep and SUVmean (r ¼ 0.562, P ¼ 0.002). No significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…Whereas in our study no statistically significant correlation was seen overall between either k ep or K trans and SUVmax, a previous study of rectal cancer patient did demonstrate a significant positive correlation between k ep and SUVmax [37]. However, in a study of colorectal liver metastases, no association was seen between vascular parameters (k ep , V e , and K trans ) and glucose metabolism [38], which is concordant with our study.…”
Section: Discussionsupporting
confidence: 90%
“…Whereas in our study no statistically significant correlation was seen overall between either k ep or K trans and SUVmax, a previous study of rectal cancer patient did demonstrate a significant positive correlation between k ep and SUVmax [37]. However, in a study of colorectal liver metastases, no association was seen between vascular parameters (k ep , V e , and K trans ) and glucose metabolism [38], which is concordant with our study.…”
Section: Discussionsupporting
confidence: 90%
“…MRI signal intensity is dependent on many factors, including native tissue relaxation rates, contrast agent dose, injection rate, choice of imaging sequence and parameters, machine gain, and scaling factors 22. Therefore, semiquantitative results are not readily applicable from one institution to another, because of different imaging equipment and protocol 23,24. The advantage of semiquantitative analysis is that it is relatively simple in estimating with T1-weighted MRI, whereas quantitative analysis requires conversion of MRI signal intensities to contrast concentration by complex pharmacokinetic modeling 10.…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al (2011) reported moderate and strong relationship between K trans and clinicopathological elements, K trans might be the prognostic indicator of rectal cancer. Gu et al (2011) found a positive correlations between k ep and SUV values in primary rectal adenocarcinomas suggesting an association between angiogenesis and metabolic activity and further reflecting that angiogenic activity in washout phase is better associated with tumor metabolism than the uptake phase. Although these encouraging results, the evaluation after neo-adjuvant therapy remains actually difficult in borderline cases where an overestimation is the most common drawback.…”
Section: Dce-mri In Rectal Cancermentioning
confidence: 70%